Spinal Cord Injury as a Model of Bone-Muscle Interactions: Therapeutic Implications From in vitro and in vivo Studies - Invernizzi, Marco; de Sire, Alessandro; Renò, Filippo; Cisari, Carlo; Runza, Letterio; Baricich, Alessio; Carda, Stefano; Fusco, Nicola (Frontiers in Endocrinology, 2020)
Spinal cord injuries (SCIs) represent a variety of conditions related to the damage of the spinal cord with consequent musculoskeletal repercussions. The bone and muscle tissues share several catabolic pathways that lead to patients’ disabilities in SCI patients. In this second part of the review article, we provide a comprehensive characterization of the available treatment options targeting the skeleton and the bone in SCI patients. Among the pharmacological intervention, bisphosphonates, anti-sclerostin monoclonal antibodies, hydrogen sulfide, parathyroid hormone, and RANKL pathway inhibitors represent valuable options for treating bone alterations. Loss phenomena at the level of the muscle can be counteracted with testosterone, anabolic-androgenic steroids, and selective androgen receptor modulators. Exercise and physical therapy are crucial strategies to increase bone and muscle mass. Nutritional interventions could foster SCI treatment, particularly in the setting of synergistic and multidisciplinary interventions, but there are no specific guidelines available to date. The development of multidisciplinary recommendations is required to allow for proper clinical management of SCI patients.